2021
DOI: 10.13005/bpj/2331
|View full text |Cite
|
Sign up to set email alerts
|

In silico Docking Studies of Antiglycation Activity of Isorhamnetin on Molecular Proteins of Advanced Glycation end Product (AGE) Pathway

Abstract: Advanced glycation end products (AGEs) are formed excessively in pathological conditions due to non - enzymatic glycation of proteins, lipids or nucleic acids, affecting their structure and function. Isorhamnetin is a naturally occurring flavonoid with anti-inflammatory, anti-oxidant, anti-obesity, anticancer, anti-diabetic and anti-atherosclerosis activity. Structure activity studies of isorhamnetin reveal the presence of hydroxyl group in the B-ring of isorhamnetin may contribute to antiglycation activity. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The action of transcription factors leads to insulin resistance, inflammation, oxidative stress, apoptosis, and also autophagy. In diabetes, AGEs-RAGE signaling is overexpressed, which is a direct cause of diabetic complications ( Pathomthongtaweechai and Chutipongtanate, 2020 ; Shen et al, 2020 ; Sindhuja et al, 2021 ) ( Figure 2 ). Verapamil showed satisfactory affinity (no lower than −4.6 kcal/mol) for all seventeen proteins, possibly restoring their initial physiological function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The action of transcription factors leads to insulin resistance, inflammation, oxidative stress, apoptosis, and also autophagy. In diabetes, AGEs-RAGE signaling is overexpressed, which is a direct cause of diabetic complications ( Pathomthongtaweechai and Chutipongtanate, 2020 ; Shen et al, 2020 ; Sindhuja et al, 2021 ) ( Figure 2 ). Verapamil showed satisfactory affinity (no lower than −4.6 kcal/mol) for all seventeen proteins, possibly restoring their initial physiological function.…”
Section: Resultsmentioning
confidence: 99%
“…This promotes inflammation, oxidative stress, and structural changes in blood vessels, ultimately leading to complications such as atherosclerosis, nephropathy, retinopathy, and impaired vascular function. A molecular docking for AGE pathway proteins revealed that verapamil may owe its antiglycative properties in vivo ( Pathomthongtaweechai and Chutipongtanate, 2020 ; Shen et al, 2020 ; Sindhuja et al, 2021 ). The drug presented a good docking ability to all tested ligands, starting at −4.6 kcal/mol for ATF4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exhaustiveness parameter was set at a level of 8. Finally, PyMOL 2.5 allowed us to visualize the possible molecular docking. , , …”
Section: Bovine Serum Albumin (Bsa) Modelmentioning
confidence: 99%
“…Another mechanism of action of antiglycation compounds is by binding to their receptors, this can cause cellular mechanisms due to the interaction of AGEs with their receptors to be inhibited (Sindhuja et al, 2021). Orchids also contain polyphenols, such as Bauhinia variegate (Abdel-Halim et al, 2020).…”
Section: Antiglycation Potentialmentioning
confidence: 99%